Phenotypic Variability and mTOR Pathway Gene Aberrations in Familial Tuberous Sclerosis - Liang, Winnie S.; Sekar, Shobana; Nasser, Sara; Adkins, Jonathan; Cuyugan, Lori; Enriquez, Daniel; Rangasamy, Sampath; Narayanan, Vinodh (Journal of Pediatric Neurology, 2017)
Tuberous sclerosis complex (TSC) is an autosomal dominant disorder that demonstrates variable severity, such that affected family members may have mild or severe disease. We performed exome and RNA sequencing of blood leukocytes from mild and severe cases across four families to identify mTOR pathway aberrations that may underlie phenotypic variability. In each family, we identified TSC1/TSC2 aberrations along with different mTOR pathway gene alterations, including base substitutions, deletions, and skewed allelic frequencies. Here, we describe the first reported DNA and RNA analysis of TSC families demonstrating mTOR pathway aberrations in mild and severe forms of the disease.
Keywords: familial tuberous sclerosis; phenotypic variability; next generation sequencing